2013
DOI: 10.12657/denbio.070.011
|View full text |Cite
|
Sign up to set email alerts
|

Climatic response of Betula ermanii along an altitudinal gradient in the northern slope of Changbai Mountain, China

Abstract: Abstract:The sensitivity of Betula ermanii tree-ring growth to climate variation over an altitudinal gradient was assessed. Betula ermanii forest grows in the northern slope of Changbai Mountain from approximately 1,700 m above sea level (a.s.l.), and forms the upper tree line at nearly 2,100 m a.s.l.. Six study sites were constructed along the altitudinal gradient (1,670 to 2,010 m a.s.l.) and ring-width chronologies of Betula ermanii were built. The mean tree-ring series intercorrelation (RBAR) increased wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
1
14
1
Order By: Relevance
“…The inverse growth response was mainly due to the habitat difference. High temperatures during the growing season can improve the photosynthesis rate and increase the pool of stored carbohydrates for tree growth [53], however, higher temperatures could cause higher stand respiration and evaporation, consequently resulting in water deficits which may inhibit radial growth [54]. P. likiangensis and A. georgei are shade-tolerant species, growing in the shaded and half-shaded slopes with less radiation and evaporation and, therefore, higher amounts of moisture are available for tree growth.…”
Section: Divergent Effects Of Common Climatic Factors Among Speciesmentioning
confidence: 99%
“…The inverse growth response was mainly due to the habitat difference. High temperatures during the growing season can improve the photosynthesis rate and increase the pool of stored carbohydrates for tree growth [53], however, higher temperatures could cause higher stand respiration and evaporation, consequently resulting in water deficits which may inhibit radial growth [54]. P. likiangensis and A. georgei are shade-tolerant species, growing in the shaded and half-shaded slopes with less radiation and evaporation and, therefore, higher amounts of moisture are available for tree growth.…”
Section: Divergent Effects Of Common Climatic Factors Among Speciesmentioning
confidence: 99%
“…Betula ermanii, a deciduous broad-leaved tree species, is widely distributed in open spaces of steep mountain slopes and/or boreal forests, mainly in Japan, in the Russian Far East and in Northeast China (Takahashi et al, 2005;Sano et al, 2010;Wang et al, 2013), where few conifers are even able to survive. Previous research has assessed its tree-ring growth (Takahashi et al, 2005;Yu et al, 2007;Wang et al, 2013), frost resistance (Gansert et al, 1999), and the microfungi associated with its leaf litter and their response to climate variation over an altitudinal gradient (Osono and Hirose, 2009). Betula ermanii has a lifespan of about 250 years near the timberline, due to slow growth in a consistently cold environment (Sano et al, 2010).…”
Section: Host and Sitementioning
confidence: 99%
“…Our sampled area comprised pure stands of B. ermanii with an open canopy, as well as the timberline of the CNR. Previous studies showed that the growth of B. ermanii along this gradient was very sensitive to climate variation (Wang et al ., ), and will likely respond strongly to climate warming, especially in the upper birch forest close to the timberline (He et al ., ). The value of using this timberline tree species as FEs' host is that they are a dominant species across a wide elevation range, allowing examination of both climatic and host variables on assemblage patterns across this subalpine gradient.…”
Section: Introductionmentioning
confidence: 97%
“…Tree-ring records are often used to investigate the responses of tree growth to historical climate variations, to predict the effects of future climate change on tree growth, and to understand the spatial and temporal patterns of tree-growth variability of forest ecosystems [5][6][7]. Therefore, tree-ring records can increase our capacity to predict potential changes in forest structure and composition, as well as provide important information on natural resource management [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%